Engaging Adolescents Through Participatory and Qualitative Research Methods to Develop a Digital Communication Intervention to Reduce Adolescent Obesity. (August 2017) - Livingood, William C.; Monticalvo, David; Bernhardt, Jay M.; Wells, Kelli T.; Harris, Todd; Kee, Kadra; Hayes, Johnathan; George, Donald; Woodhouse, Lynn D.
Background . The complexity of the childhood obesity epidemic requires the application of community-based participatory research (CBPR) in a manner that can transcend multiple communities of stakeholders, including youth, the broader community, and the community of health care providers. Aim . To (a) describe participatory processes for engaging youth within context of CBPR and broader community, (b) share youth-engaged research findings related to the use of digital communication and implications for adolescent obesity intervention research, and (c) describe and discuss lessons learned from participatory approaches. Method . CBPR principles and qualitative methods were synergistically applied in a predominantly African American part of the city that experiences major obesity-related issues. A Youth Research Advisory Board was developed to deeply engage youth in research that was integrated with other community-based efforts, including an academic–community partnership, a city-wide obesity coalition, and a primary care practice research network. Volunteers from the youth board were trained to apply qualitative methods, including facilitating focus group interviews and analyzing and interpreting data with the goal of informing a primary care provider–based obesity reduction intervention. Results . The primary results of these efforts were the development of critical insights about adolescent use of digital communication and the potential importance of messaging, mobile and computer apps, gaming, wearable technology, and rapid changes in youth communication and use of digital technology in developing adolescent nutrition and physical activity health promotion. Conclusions . The youth led work helped identify key elements for a digital communication intervention that was sensitive and responsive to urban youth. Many valuable lessons were also learned from 3 years of partnerships and collaborations, providing important insights on applying CBPR with minority youth populations.